2019
DOI: 10.3390/ma12132168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sodium and Potassium Nitrate Contaminated Polyaniline-Poly (Ethylene Oxide) Composites Synthesized via Facile Solution Casting Technique

Abstract: Fabrication of composites by developing simple techniques can be an effective way to modify some properties of individual materials. The present study relates to facile synthesis of sodium nitrate (NaNO3) and potassium nitrate (KNO3) contaminated polyaniline (PANI) and poly (ethylene oxide) (PEO) composites without using any additives, plasticizers, or fibers. The physic-chemical and rheological properties of synthesized composites were analyzed. The composites showed enhancement in both storage and loss modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…30−32 On the other hand, combination of PANI with various polymers/nanomaterials to form blends or composites can be a facile method for the improvement of its mechanical properties. 30,33 For example, Bilal et al studied the rheological properties of polyaniline−poly(ethylene oxide) (PANI-PEO) and their composites with KNO 3 and NaNO 3 . They reported that pyridine is the best solvent for the rheological measure-ments.…”
Section: Structure and Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…30−32 On the other hand, combination of PANI with various polymers/nanomaterials to form blends or composites can be a facile method for the improvement of its mechanical properties. 30,33 For example, Bilal et al studied the rheological properties of polyaniline−poly(ethylene oxide) (PANI-PEO) and their composites with KNO 3 and NaNO 3 . They reported that pyridine is the best solvent for the rheological measure-ments.…”
Section: Structure and Propertiesmentioning
confidence: 99%
“…10 °C, the pure PANI-PEO has a lower viscosity than the PANI-PEO-KNO 3 composite, and the viscosities of both composites drop by increasing the temperature to 20 °C. 30 Apart from organic solutions, the rheological properties of the aqueous PANI blends, e.g., polyaniline−poly(vinylpyrrolidone) (PVP) dispersion, have also been investigated. The PANI-PVP dispersion is stable enough showing no gelation of precipitates.…”
Section: Structure and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations